2019
DOI: 10.3389/fpls.2019.00216
|View full text |Cite
|
Sign up to set email alerts
|

The DOF Transcription Factor SlDOF10 Regulates Vascular Tissue Formation During Ovary Development in Tomato

Abstract: The formation of fruits is an important step in the life cycle of flowering plants. The process of fruit development is highly regulated and involves the interaction of a complex regulatory network of genes in both space and time. To identify regulatory genes involved in fruit initiation in tomato we analyzed the transcriptomic profile of ovaries from the parthenocarpic PsEND1:barnase transgenic line. This line was generated using the cytotoxic gene barnase targeted to the anthers with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“… Wen et al (2016) found that CsDof TF might play a role against biotic stresses in cucumber ( Cucumis sativus ). Rojas-Gracia et al (2019) stated the SIDOF10 TF involved regulation of vascular tissue in tomatoes ( Solanum lycopersicum ). C2H2 TF regulates abiotic stress responses in plants ( Han et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“… Wen et al (2016) found that CsDof TF might play a role against biotic stresses in cucumber ( Cucumis sativus ). Rojas-Gracia et al (2019) stated the SIDOF10 TF involved regulation of vascular tissue in tomatoes ( Solanum lycopersicum ). C2H2 TF regulates abiotic stress responses in plants ( Han et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of the AtDOF2.4/PEAR1 (PHLOEM EARLY DOF1), AtDOF5.1/PEAR2 (PHLOEM EARLY DOF2), AtDOF3.2/DOF6, AtDOF5.3/TMO6, AtDOF1.1/OBP2 (OBF BINDING PROTEIN2) and AtDOF5.6/HCA2 (HIGH CAMBIAL ACTIVITY2) genes was reported to be regulated by auxin and cytokinin in the sieve tube of the primary phloem (Miyashima et al, 2019;Smetana et al, 2019). Downregulation of tomato SlDOF10 triggered parthenocarpic development while suppressing vascular tissue development (Rojas-Gracia et al, 2019). MdDOF15, MdDOF18, and MdDOF48 were significantly upregulated in apple during pollen tube growth and development (Yang et al, 2018b).…”
Section: Functions Of Dofs In Plant Growth and Developmentmentioning
confidence: 99%
“…In addition, these male sterile plants could be used in hybrid breeding applications as very convenient parental lines. The transgenic lines generated could also be useful tools to investigate the molecular mechanisms accountable for the observed metabolic phenotypes, and also to understand the connection between impaired anther development and parthenocarpy (Medina et al, 2013; Rojas-Gracia et al, 2017, 2019).…”
Section: Side Effects In the Psend1::barnase-barstar Male Sterile Plamentioning
confidence: 99%